A paz tensa da chama fugaz: a configuração do amor no romance contemporâneo, Lygia Fagundes Telles e Lídia Jorge - Costa, Maria Aparecida da (2014)
This thesis A paz tensa da chama fugaz: a configuração do amor no romance contemporâneo, Lygia Fagundes Telles e Lídia Jorge aims to study the configuration of Love in contemporary novels. Their corpuses of study are the novels As horas nuas (1989), by the Brazilian writer Lygia Fagundes Telles; and O vento assobiando nas gruas (2002), by the Portuguese writer Lídia Jorge. The following research tries to understand how the characters from those texts deal with some love questions on the context of the contemporary narrative; it also tries to comprehend the love expression which is formed as a contradictorily fluid feeling and intensely wanted, which are important points concerning the love discourse at the present day. As a critic-comparative study, this research focuses on the problematic concerned love as a synonym of Eros, in other words, the relation between lovers, analyzed through social and philosophical perspective. Through that, this work broadens the study of two contemporary novels, and it also establish connections between the characters from those novels and the literary environment where they are placed, once it focuses on the human and social context presented in this books. The thesis ends calling attention to the dichotomy of love and death, to the image of love which grows through absence and through the longing of completeness of the human being; that is why this work sustains that the Lygia Fagundes Telles and Lídia Jorge update and materialized in their texts the plurality of contemporary love conception, which continues to be contradictory, fragmented and problematic